Assessing the applicability of protein residues in combination with lipid residues to reconstruct Indus foodways from Gujarat - Kalyan Sekhar Chakraborty; Lindsey Paskulin; Prabodh Shirvalkar; Yadubirsingh Rawat; Heather M.-L. Miller; Greg Slater; Camilla Speller (Quaternary Environments and Humans)
When extracted and analysed in tandem, proteomics and lipid residue analysis can provide high resolution identification of ancient foodstuff. Here, we apply lipid residue and shotgun proteomic analyses to 11 ceramic vessel sherds from the Gujarat, India-based Indus Valley Civilization site of Kotada Bhadli. Our results demonstrate variable success. Lipids were successfully recovered from each ceramic vessel and suggest the presence of dairy and meat from cattle/buffalo, and meat from sheep/goat and monogastric animals, such as pigs and birds. Additionally, we were also able to identify the presence of plant products such as leafy vegetables, oils and broomcorn millets. In contrast, none of the extracted proteins could be confidently traced to specific foods or ingredients and were thus unable to contribute to broader interpretations of foodways at Kotada Bhadli. Nevertheless, our results present an opportunity to discuss pathways for improving proteomic methods, and advocate for the need to report negative results as well as positive ones. We support continued efforts to apply multi-proxy approaches to the study of ancient ceramics and consider future applications of shotgun proteomics in this rapidly evolving field.